Effects of different frying methods, frying conditions and pre-treatments on formation of aldehydes in french fries - Zakaria, Adilah (2016)
Aldehydes are the decomposed compounds formed by the thermal decomposition and oxidation of cooking oil during frying. The formation of such oxidation compounds in the frying oil is one of the most critical concerns for consumers. In most cases, they are known as unhealthy compounds, which cause many health issues (such as cardiovascular diseases) in the human. This study aimed to investigate the effects of different frying methods (i.e. deep fat frying, microwave frying and air frying), conditions (time and temperature) and pre-treatments (i.e. blanching, freezing and drying) on the formation and reduction of different aldehydes in frying oil and French fries. The results showed that the main detected aldehydes were decanal, 2-decenal, 2, 4-decadienal, hexanal, 2-heptenal and nonanal. Both frying methods and conditions significantly (p<0.05) affected the type and content of aldehydes formed in the oil and French fries during frying. Total aldehyde content was considerably increased by increasing frying time and temperature. The significant changes in aldehyde content during frying were significantly related to the changes in peroxide value (PV), anisidine value (AV), totox value (TV), free fatty acid (FFA) and iodine value (IV). The application of the deep frying and air frying resulted in the formation of the highest and the lowest aldehyde content in the frying oil and French fries. The deepfried samples showed the highest concentration of hexanal (14.2 ppm), 2-heptenal (3.1 ppm), nonanal (1.4 ppm), 2 decenal (2.2 ppm) and 2, 4-decadienal (4.3 ppm); while air-fried samples showed the lowest concentration in hexanal (0.6 ppm), 2-decenal (0.3 ppm) and 2, 4-decadienal (0.2 ppm). The results revealed that the pre-treatments of potato also significantly (p<0.05) influenced the formation and reduction of aldehydes in the oil during frying. Among all applied pre-treatments, the drying resulted in the lowest concentration of aldehydes (ppm) namely hexanal, 2-heptenal, nonanal and decanal. Meanwhile, the blanching followed by freezing resulted in the formation of the highest aldehyde content. This might be explained by the significant effect of such pre-treatments on the moistutre content. In fact, the moisture content of potato significantly affected the formation rate and content of aldehydes in French fries and oil. This might be because the samples containing higher moisture contents are more susceptible against hydrolysis and oxidation, resulting in the formation of higher aldehyde content. It was concluded that the selection the proper frying method and condition can significantly affect the type and content of aldehydes during frying. The current study revealed that the deep frying and air frying were the least and most desirable frying method among all applied methods. The current study highly recommended to apply drying process in order to reduce moisture content and making healthier French fries with lower level of aldehyde content.